2018
DOI: 10.1111/anu.12801
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of chitin deacetylase 1 from Macrobrachium nipponense , and the effects of dietary protein on growth, body composition and digestive enzymes

Abstract: The optimal protein level in the diet of Oriental river prawn was investigated. Four isocaloric diets containing 300 g/kg, 360 g/kg, 420 g/kg, 480 g/kg crude protein (casein) were tested. Prawns fed 420 g/kg or 480 g/kg protein exhibited higher weight gain, specific growth rate, hepatopancreas somatic indices, feed coefficient and survival rate. Trypsin activity in the hepatopancreas increased with increasing dietary protein, with no significant difference between 420 g/kg and 480 g/kg groups (p < 0.05). Amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Shrimp are an excellent source of protein, minerals and vitamins, especially essential amino acids such as lysine, tryptophan and phenylalanine (Fan et al 2018). The composition and concentration of amino acids in shrimp muscle may affect its quality (Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp are an excellent source of protein, minerals and vitamins, especially essential amino acids such as lysine, tryptophan and phenylalanine (Fan et al 2018). The composition and concentration of amino acids in shrimp muscle may affect its quality (Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the present study identified six chitinases and found that they showed differential expression patterns in stages PoM, InM, and PrM, suggesting different physiological roles and modes of action of during the molting cycle. The chitin deacetylase gene is another chitin metabolism-related gene involved in the catalysis of the acetamido group in the N-acetyl-d-glucosamine units of chitin 49 , 50 . To date, five classes of chitin deacetylase have been characterized, three of which were identified in this study (chitin deacetylase 1, chitin deacetylase 4, and chitin deacetylase 9).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identi ed six chitinases and found that they showed differential expression patterns in stages PoM, InM, and PrM, suggesting different physiological roles and modes of action of during the molting cycle. The chitin deacetylase gene is another chitin metabolism-related gene involved in the catalysis of the acetamido group in the N-acetyl-d-glucosamine units of chitin [44,45]. To date, ve classes of chitin deacetylase have been characterized, three of which were identi ed in this study (chitin deacetylase 1, chitin deacetylase 4, and chitin deacetylase 9).…”
Section: Expression Patterns Of Degs Associated With Cuticle and Cytomentioning
confidence: 99%
“…To date, ve classes of chitin deacetylase have been characterized, three of which were identi ed in this study (chitin deacetylase 1, chitin deacetylase 4, and chitin deacetylase 9). In insects, it has been demonstrated that the chitin deacetylase gene is involved not only in growth but also in the immune system [45,46]. However, few studies have charactered the chitin deacetylase genes or studied their function in the molting cycle of crustaceans.…”
Section: Expression Patterns Of Degs Associated With Cuticle and Cytomentioning
confidence: 99%